EFEKTIVITAS INSTAGRAM DALAM MENINGKATKAN PENGETAHUAN SADARI SEBAGAI PENCEGAHAN DINI KANKER PAYUDARA - Ervi Rachma Dewi; Lutfi Nihayani (Universitas Pahlawan, 2021)
Breast cancer is one of the cancers that cause women's death, because women who fail to realize why they have cancer. The high risk of breast cancer is caused by breast cancer education since adolescents in protection and early breast cancer. Based on the initial survey, it was found that 92.5% of 40 teenagers in Kudus did not know BSE, and 7.5% of 40 teenagers had heard the term BSE. Instagram as one of the information media that is widely used today can be used as a health promotion media. This research reveals knowledge of Instagram social media in increasing BSE knowledge as an early increase in cancer in adolescents in the Kudus district. The type and design of this study was pre- experimental with the One Group Pretest-Posttest Design. The sample in this study was adolescents in various high schools in Kudus Regency with 90 adolescents. The research instrument was questionnaire and Instagram media with AISAS. The data analysis of this research is univariate analysis to determine the level of knowledge and media instagram with AISAS while the bivariate analysis using Wilcoxon test. Based on the results of the study the average value before intervention 47.78 and intervention 74.50, the level of awareness of adolescents about BSE both 46 (51.1%) and sufficient 44 (48.9%) with the Wilcoxon test results obtained a value of 0, 0001 (p